2011
DOI: 10.1183/09031936.00004711
|View full text |Cite
|
Sign up to set email alerts
|

Serum CC chemokine ligand-18 predicts lung disease worsening in systemic sclerosis

Abstract: Elevated serum CC chemokine ligand (CCL)18 reflects lung fibrosis activity in systemic sclerosis (SSc) and could be an early marker of lung function worsening. Therefore, we sought to evaluate whether serum CCL18 levels at baseline could predict worsening of lung disease in SSc.In this prospective study, 83 SSc patients were analysed longitudinally over a 4-yr observation period for the risk of occurrence of combined deleterious events, defined as a 10% decrease from baseline of total lung capacity or forced v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
68
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 30 publications
4
68
1
Order By: Relevance
“…TIEV et al [1] demonstrated very nicely that elevated CC chemokine ligand 18 (CCL18) serum levels predict lung disease progression in patients with systemic sclerosis (SSc). In the multivariate analysis, the hazard ratio for lung function worsening or death was 5.36 for SSc patients with serum CCL18 concentration above 187 ng?mL -1 .…”
Section: Serum Ccl18 Is Predictive For Lung Disease Progression and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…TIEV et al [1] demonstrated very nicely that elevated CC chemokine ligand 18 (CCL18) serum levels predict lung disease progression in patients with systemic sclerosis (SSc). In the multivariate analysis, the hazard ratio for lung function worsening or death was 5.36 for SSc patients with serum CCL18 concentration above 187 ng?mL -1 .…”
Section: Serum Ccl18 Is Predictive For Lung Disease Progression and Mmentioning
confidence: 99%
“…We read with pleasure the article ''Serum CC chemokine ligand-18 predicts lung disease worsening in systemic sclerosis'' [1], published in the European Respiratory Journal. TIEV et al [1] demonstrated very nicely that elevated CC chemokine ligand 18 (CCL18) serum levels predict lung disease progression in patients with systemic sclerosis (SSc).…”
Section: Serum Ccl18 Is Predictive For Lung Disease Progression and Mmentioning
confidence: 99%
“…CCL18 can stimulate fibroblast collagen and has been found to be increased in serum and bronchoalveolar lavage (BAL) fluid in a number of fibrotic lung diseases, including SSc-ILD 16 . Three longitudinal studies with a total of 116 patients with SSc-ILD investigated the correlation of serum CCL18 with ILD activity determined by HRCT, lung function, and BAL analysis, with promising results 16,17,18 . Tiev, et al analyzed serum CCL18 levels in 83 SSc patients with ILD over a 4-year followup period 18 .…”
mentioning
confidence: 99%
“…Three longitudinal studies with a total of 116 patients with SSc-ILD investigated the correlation of serum CCL18 with ILD activity determined by HRCT, lung function, and BAL analysis, with promising results 16,17,18 . Tiev, et al analyzed serum CCL18 levels in 83 SSc patients with ILD over a 4-year followup period 18 . At a cutoff level of 187 ng/ml for identifying subsequent worsening of lung disease within 2 years or death, serum CCL18 was independently predictive of worsening ILD (HR = 5.4; p = 0001) 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation